Laparo-endoscopic single-site left adrenalectomy using conventional ports and instruments - Deepraj S Bhandarkar (Urology Annals, 2014)
Laparo-endoscopic single-site adrenalectomy (LESS-A) is commonly performed using specialized access devices and/or instruments. We report a LESS-A in a 47-year-old woman with a left aldosteranoma via a subcostal approach utilizing conventional laparoscopic ports and instruments. The feasibility and cost-effectiveness of this approach are highlighted and the literature on the subject is reviewed.